Libras em saúde: avaliação dos pacientes surdos frente ao atendimento médico e a perspectiva de atendimento dos acadêmicos de medicina da Universidade Federal do Pará - VASCONCELOS, Sidney dos Santos (2019)
The meeting between health professionals and deaf patients is usually marked by difficulty in communication. While it is a right of people with disabilities to have access to quality health services, they are often taken care of incorrectly and even in some cases are disrespected in their condition, since health services they do not have professionals capable of attending excellence to them. The physician should have the ability to communicate with patients who may or may not have these characteristics. In the context of much accessibility, it is important to disseminate knowledge about Libras among students of health courses, to contribute to the training of professionals capable of understanding and assisting the needs of those who use it as their first language. The objective of this study is to investigate the expansion of knowledge about the need for access to the hearing impaired to health services. Methodology: This is a quantitative study with a descriptive and crosssectional study design and is part of the project Libras em Saúde of the NGO IFMSA BRAZIL (Federal Federation of Medical Students Association of Brazil), a committee of the Federal University of Pará, whose general objective is to investigate the attention to the deaf person in the health area from the academic perspective, and also from the deaf person. Twenty deaf people, 12 men and 08 women, participated in the study. Bilingual and communicating for pounds. The percentage of negative evaluations of the meeting with health professionals represented 51% among bilinguals; and 78% in the group of deaf people who communicate. We interviewed 56 academics from the third and fourth years of UFPA medicine. The pre-test evidenced students' lack of knowledge about deaf culture and sign language. In the post-test: the students were able to differentiate the deaf from the hearing impaired by insertion or not in the deaf culture. The inclusion of the teaching of Libras as a discipline of the medical course, becomes an important instrument of change in the social reality that the hearing impaired is currently included